2013
DOI: 10.1002/jbm.a.34815
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory response and bone healing capacity of two porous calcium phosphate ceramics in critical size cortical bone defects

Abstract: In the present study, two open porous calcium phosphate ceramics, β-tricalcium phosphate (β-TCP), and hydroxyapatite (HA) were compared in a critical-sized femoral defect in rats. Previous comparisons of these two ceramics showed significantly greater osteoinductive potential of β-TCP upon intramuscular implantation and a better performance in a spinal fusion model in dogs. Results of the current study also showed significantly more bone formation in defects grafted with β-TCP compared to HA; however, both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 27 publications
1
14
0
1
Order By: Relevance
“…Is there data from this or earlier studies from your lab using this model to confirm this is a critical sized defect? Authors: The critical size of this bone defect using this fixation method has been confirmed by our group in two published studies (Chatterjea et al, 2013;van der Stok et al, 2013a, text references). In these studies, untreated defects did not show spontaneous bridging up to 12 weeks.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…Is there data from this or earlier studies from your lab using this model to confirm this is a critical sized defect? Authors: The critical size of this bone defect using this fixation method has been confirmed by our group in two published studies (Chatterjea et al, 2013;van der Stok et al, 2013a, text references). In these studies, untreated defects did not show spontaneous bridging up to 12 weeks.…”
Section: Resultssupporting
confidence: 52%
“…The standard deviation of BV formed was estimated to be ~50 % based on previous work (Chatterjea et al, 2013; Van der Stok et al, 2013a; Van der Stok et al, 2013b). A simple power calculation using a Students' t-test with a β-value of 0.8 indicates that both groups should consist of a minimum of 5 rats.…”
Section: Statisticsmentioning
confidence: 99%
“…The research in our group also demonstrated that the osteoinductive ceramics could regulate the macrophages response by influencing their attachment, morphology, and cytokines secretion (Chen et al, ). Biomaterials had also been engineered as components of the complex living systems and functioned in tissue repair and other metabolic process (Aikawa et al, ; Chatterjea et al, ). It is conspicuously that the role of inflammation in tissue repair and regeneration is more than negative.…”
Section: Introductionmentioning
confidence: 99%
“…The latter ability is necessary to avoid a possible risk that the strong spacer implanted in the tibia may cause an obstacle in revision surgery after HTO [32]. Therefore, it can be useful to assess the osteoconductivity and [6,9,12,15,19,23,24,27,43,45]. However, the experimental conditions used in these basic studies are different from the biological and biomechanical environments surrounding synthetic spacers implanted into the tibia of patients.…”
Section: Introductionmentioning
confidence: 99%